ABC Transporters and the Alzheimer’s Disease Enigma - Wolf, Andrea; Bauer, Bjoern; Hartz, Anika M. (Frontiers in Psychiatry, 2012)
Alzheimer’s disease (AD) is considered the “disease of the 21st century”. With a 10-fold increase in global incidence over the past 100 years, AD is now reaching epidemic proportions and by all projections, AD patient numbers will continue to rise. Despite intense research efforts, AD remains a mystery and effective therapies are still unavailable. This represents an unmet need resulting in clinical, social, and economic problems. Over the last decade, a new AD research focus has emerged: ATP-binding cassette (ABC) transporters. In this article, we provide an overview of the ABC transporters ABCA1, ABCA2, P-glycoprotein (ABCB1), Mrp1 (ABCC1) and BCRP (ABCG2), all of which are expressed in the brain and have been implicated in AD. We summarize recent findings on the role of these five transporters in AD, and discuss their potential to serve as therapeutic targets.